Effectiveness of In-game Advertisement: An Examination of Repetition Effect, Brand Familiarity and the Relationship Between Gaming Skills and Advertising Execution. Issue 1 (2nd January 2017) - Kim, Yongjae; Leng, Ho Keat
ABSTRACT: The aim of this study is to examine whether repeated exposure to brands in sport video games affects brand awareness, attitudes, and purchase intention. In addition, it will also examine the effect of brand familiarity and the relationship of gaming skills and different types of in-game advertising on brand awareness. For the purpose of this study, an experimental research design was employed by varying the number of exposures to advertisement messages in sport video games. The findings show that repetitive game play has a significant and positive effect on brand recall and recognition rate, attitudes toward the brand, and intention to purchase the brands. Similar to other studies, it found that brand familiarity has a positive effect on brand awareness. In addition, the findings suggest that the cognitive effects of the in-game advertising type depend on gaming skills. This suggests that in-game advertisements may be more effective than previously thought.